FLUX AND REJECTION CHARACTERISTICS OF AMINE WASTEWATER USING MEMBRANE SEPARATION PROCESSES - WOLDEHAWARIAT, BINYAM SEYOUM (2010)
Sour natural gas must be purified by removing various impurities, including acid gases particularly carbon dioxide and hydrogen sulfide before it can be utilized. Various amine solutions such as monoethanolamine (MEA), methyldiethanolamine (MDEA) and diethanolamine (DEA) are used for the absorption of these gases. During the absorption-desorption process, a small amount of amines carry-over and discharged to the effluent stream. Treatment of this wastewater which contains high COD content using existing biological treatment is not suitable since the wastewater can endanger the activated sludge. Thus, the main objective of this study is to investigate the removal of amines, namely MEA, MDEA and DEA from artificial wastewater using membrane separation processes. The experimental studies were conducted to evaluate the permeate flux and observed rejection of artificial amines wastewaters using AFC99, AFC40 and CA202 membranes by varying the operating pressure, cross-flow velocity, feed concentration and pH. Two membrane transport models, namely combined film theory–solution diffusion (CFSD) and combined film theory–Spiegler Kedem (CFSK) models were used in order to estimate the membrane transport parameters and predict their rejection performances. The experimental study shows that the permeate flux is linearly increased with operating pressure. The percentage of rejection was found to be depending on the type of amines used as well as the operating conditions selected. Results showed that the observed rejection was found to be increasing with the increase in operating pressure and cross-flow velocity, whereas was found to be decreasing with the increases in feed concentration. In addition, the observed rejection was also found to be increasing as the pH of the feed decreases from 8 to 3. The findings also showed that AFC99 membrane exhibited the best rejection efficiency in all amines solutions followed by AFC40 and CA202 membranes. AFC99 membrane was able to reject more than 96% for all amines under the present study. On the other hand, the AFC40 and CA202 membranes were able to reject MEA up to 70% and 30 %, respectively, and for MDEA up to 94 % and 38%, respectively. The estimated transport parameters obtained from CFSD and CFSK models, including the solute transport parameter, reflection coefficient and mass transfer coefficients were found to be depending on the feed concentration and cross-flow velocity. For both models, the solute transport parameter was found to be increasing with cross-flow velocity and feed concentration. Similarly, the mass transfer coefficient and reflection coefficients also increased with cross-flow velocity, but both were found to be decreasing with the increase in feed concentration. All trends obtained from this work are consistent with the cited literatures. The validation study shows that the CFSD and CFSK models predictions are in excellent agreement with the experimental results. In conclusion, membrane processes particularly reverse osmosis (with the application of AFC99 membrane in the present study) can be effectively used to remove various types of amines present in the wastewater using a single process. Similarly, nanofiltration and ultrafiltration membranes such as AFC40 and CA202 can also be selected for the same purpose but both are more suitable to be employed for complementing the existing biological treatment.